Productivity and profitability of sesame (Sesamum indicum L.) as influenced by conjoint application of nano fertilizers with conventional urea - Lal Chand Meena; Naleeni Ramawat; U. N. Shukla; P.R. Raiger; Santhosh Choudhary; Rakesh Kumar; Naresh Kumar (Annals of Agricultural Research, 2024)
A field experiment was conducted at Instructional farm, College of Agriculture, Agriculture University, Jodhpur (Rajasthan) during the kharif season 2022-23 to study the “Productivity and profitability of sesame (Sesamum indicum L.) as influenced by conjoint application of nano fertilizers with conventional urea”. Sesame variety RT-346 was planted using four levels of recommended dose of nitrogen (RDN) such as 0, 50%, 75%, 100% RDN and three level of nano-fertilizers such as seed treatment with 5ml/kg nano DAP, seed treatment with 5ml/kg nano DAP + one foliar spray of nano urea (2 ml/l of water) at 25 DAS and seed treatment with 5ml/kg nano DAP + two foliar spray of nano urea (2 ml/l of water) at 25 and 35 DAS in Factorial Randomized Block Design (FRBD) with three replications. The RDN and nano-fertilizer application had significant influence on productivity and profitability of sesame. Results indicated that application of 100% RDN gave higher length (2.6 cm), width (0.84 cm), weight (20.08 g/plant) and number of capsules/plant (32.2), number of seeds/capsule (49.2), seed yield (922 kg/ha), straw yield (2161 kg/ha) and biological yield (3026 kg/ha) over rest of the treatment but found statistically at par with 75% RDN treatment. Seed treatment with 5ml/ kg nano DAP + two foliar spray of nano urea (2 ml/l of water) at 25 and 35 DAS recorded highest length (2.6 cm), width (0.82 cm), weight (18.68 g/plant) and number of capsules/plant (33.0), number of seeds/capsule (48.7), seed yield (888 kg/ha), straw yield (2079 kg/ha) and biological yield (2911 kg/ha) over rest of the treatments but found statistically at par with seed treatment with 5ml/kg nano DAP + one foliar spray of nano urea (2 ml/l of water) at 25 DAS except weight of capsule and number of capsules/plant. The higher gross return (`71566 and 67756/ha), net return (`46002 and 41857/ha) and B:C ratio (2.80 and 2.59) was recorded under 100 % RDN and seed treatment with 5 ml/kg nano DAP + two foliar spray of nano urea (2 ml/l of water) at 25 and 35 DAS.